MODEL EKONOMETRI DATA PANEL PERTUMBUHAN EKONOMI DAERAH DI INDONESIA TAHUN 2014-2018 - Zana Chobhita Aris Tusa; Aris Soelistyo; Muhammad Sri Wahyudi Suliswanto; Muhammad Khoirul Fuddin (Jurnal Ilmu Ekonomi, 2021)
This purpose of this study was to determine domestic investment, foreign investment, and total population of economic growth, namely Gross Regional Domestic Product in 34 provinces in Indonesia in 2014-2018. This research uses quantitative methods. The type of data used is secondary obtained from the Central Statistics Agency which is ready for processing.The data collection technique used is the documentation method. The analysis technique used is panel data regression. The results of this study indicate that each variable has a positive and significant effect on economic growth. Namely Foreign Investment, Domestic Investment, and Total Population which have a positive and significant effect on economic growth.